2009
DOI: 10.1093/schbul/sbp006
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Hypothesis of Schizophrenia: Version III--The Final Common Pathway

Abstract: The dopamine hypothesis of schizophrenia has been one of the most enduring ideas in psychiatry. Initially, the emphasis was on a role of hyperdopaminergia in the etiology of schizophrenia (version I), but it was subsequently reconceptualized to specify subcortical hyperdopaminergia with prefrontal hypodopaminergia (version II). However, these hypotheses focused too narrowly on dopamine itself, conflated psychosis and schizophrenia, and predated advances in the genetics, molecular biology, and imaging research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
1,736
3
43

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,270 publications
(1,866 citation statements)
references
References 165 publications
84
1,736
3
43
Order By: Relevance
“…Deficiencies in LI and/or KB are said to reflect 'hyperassociability', whereby individuals form associations about cues which erroneously appear as salient, consistent with more recent theories proposing that psychosis can be understood in terms of aberrant salience processing [16][17][18].…”
Section: Introductionsupporting
confidence: 61%
“…Deficiencies in LI and/or KB are said to reflect 'hyperassociability', whereby individuals form associations about cues which erroneously appear as salient, consistent with more recent theories proposing that psychosis can be understood in terms of aberrant salience processing [16][17][18].…”
Section: Introductionsupporting
confidence: 61%
“…Furthermore, recent imaging genetic investigations have shown that gene polymorphisms of catechol-O-methy1 transferase [60] and DA receptor [61], which are associated with cortical DA levels, regulate the activity and connectivity strength of the MPFC and PCC/PCUN. All this strong evidence suggests a potential modulatory role of the DMN in antipsychotic medications, as all antipsychotic drugs bind to the DA receptor [62].…”
Section: Initial Studies Of the Mediating Role Of The Dmn As A Treatmmentioning
confidence: 99%
“…D2 receptor activity appears to play a key role in the metabolic rate of the striatum [78,79] and dopamine is important in the regulation of the striatum by the prefrontal cortex [80]. A significant number of gene variants associated with schizophrenia are implicated directly or indirectly in the dopaminergic system [81] and it is a possibility that the rare deletions included in the present study are disproportionately affecting this pathway. The striatum is also a key region in the interaction of the dopaminergic and glutamatergic systems [82] with a recent genetic pathway analysis strongly implicating the glutamatergic system in schizophrenia [83].…”
Section: Iq -Neuroimaging Correlationsmentioning
confidence: 84%